Older people’s participation in political organizations: The role of generativity and its impact on well-being - Serrat Fernández, Rodrigo Andrés (2017)
Aging population has increased a global concern to keep seniors active and healthy. Civic participation, in particular, has been highlighted for its social and community benefits and its impact on elders’ health and well-being. To date, however, most studies have explored volunteering; other types of civic activities, such as political participation, are largely overlooked. This study analyzes the relationship between older people’s active involvement in political organizations, generativity, and hedonic and eudaimonic well-being. We selected two samples of Spanish older people: a sample of elders actively involved in political organizations (n = 97) and a comparison group (n = 85). Measures of generative concern, hedonic well-being, and eudaimonic well-being were applied. Results showed that politically active elders obtained higher scores on generative concern than comparison group individuals. Furthermore, generative concern predicted higher scores on both eudaimonic and hedonic well-being. However, active involvement in political organizations was not related to higher levels of well-being in the multivariate analyses. Translating generative concerns into effective behaviors, for instance political activities, may imply sacrifices and efforts, such that higher levels of well-being do not necessarily result from these activities. Thus, results from this study call into question the positive effect of civic participation on elders’ well-being, showing that this may not be necessarily the case for those who are actively involved in political organizations. Future research may build on these results to compare the differential effect of different kinds of generative activities on older people’s well-being.